Menjembatani Eksplorasi dan Eksploitasi: Ambidextrous Leadership dalam Transformasi Pelayanan Publik Indonesia - Baharuddin, Aris; Herling, Herling; Sakawati, Herlina; Aina, Asri Nur; Johansyah, Oky Nur Pratiwi (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2023)
This research focuses on the concept of ambidextrous leadership in the context of public service transformation in Indonesia. The background lies in the complexity of challenges faced by the government in enhancing efficiency and innovation in public services. The objective of this study is to investigate the role of ambidextrous leadership in achieving a balance between resource exploration and exploitation efforts to enhance the quality of public services. The research methodology employs a qualitative approach with case study analysis and interviews. The findings indicate that leaders implementing ambidextrous leadership can generate significant innovations in public services while maintaining high efficiency levels, with important implications for the improvement of public services in Indonesia.